Comparación de la producción de hollín con B5 a base de aceite de ricino con diésel fósil en motores de compresión - Mafla Yépez, Carlos (2017)
The presence of soot in the environment has been considerably increasing lately according to the World Health Organization (WHO). One the cause of this issue is due to the diesel engines. The study focuses on evaluating the presence of soot on an engine by using to fuels such as Higuerilla biodiesel and fossil diesel. The test was carried out on a diesel engine test bench Mazda BT 50 with CRDi system. In order to run the tests a Braid Bee opacimeter is used (model opa 100) from the Automotive Engineering Lab in Universidad Técnica del Norte. The opacimeter is connected to a probe, which is placed at the end of the car exhaust pipe. The test consists of testing the engine into be several accelerations such as 1200, 1500, 2000, 2500 and 3000 [RPM] using Higuerilla biodiesel and fossil diesel. Once all the accelerations are completed, the opacity difference is obtained which is used to make a comparative analysis from the highest to the lowest opacity, resulting as the average percentage of opacity, which is the one that should be followed according to the established norms. It was observed a 60% reduction in diesel engine opacity with the use of Higuerilla biodiesel in relation to fossil diesel.